2017
DOI: 10.1016/j.jsat.2017.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Design and impact of bundled payment for detox and follow-up care

Abstract: Introduction Recent payment reforms promote movement from fee-for-service to alternative payment models that shift financial risk from payers to providers, incentivizing providers to manage patients’ utilization. Bundled payment, an episode-based fixed payment that includes the prices of a group of services that would typically treat an episode of care, is expanding in the United States, including mandatory models in Medicare. Bundled payment has not been developed specifically for substance use disorder (SUD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…This study provides newer national-level estimates for inpatient drug detoxification, and our results suggest a similarly low level of rehabilitation service use during inpatient detoxification. The low utilization of additional DUD treatment during inpatient detoxification may be related to a high hospital treatment cost and/or a lack of an infrastructure or organizational support to promote DUD treatment [ 10 , 42 , 43 ]. Since the 1980s, some health plans (e.g., managed care) have sought to reduce the cost of DUD treatment by shifting inpatient care toward outpatient care [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study provides newer national-level estimates for inpatient drug detoxification, and our results suggest a similarly low level of rehabilitation service use during inpatient detoxification. The low utilization of additional DUD treatment during inpatient detoxification may be related to a high hospital treatment cost and/or a lack of an infrastructure or organizational support to promote DUD treatment [ 10 , 42 , 43 ]. Since the 1980s, some health plans (e.g., managed care) have sought to reduce the cost of DUD treatment by shifting inpatient care toward outpatient care [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only 9% of those with inpatient drug detoxification in this sample were transferred at discharge, and up to 14% were considered as DAMA. They demonstrate a need to identify barriers (e.g., patient, health system, financial factors) to receiving further DUD treatments and to develop effective strategies to link the detoxification patients with outpatient or specialty treatment services for improving the continuity of DUD care [ 7 , 43 ]. Acevedo et al [ 42 ] indicated that the financial incentives or electronic reminders to medical agencies had an effect on increasing treatment use after detoxification among residential facilities.…”
Section: Discussionmentioning
confidence: 99%
“…In this literature, one can read that fee-for-service rewards volume instead of quality of care Hirsch et al, 2015) and can therefore hinder the implementation of integrated care based on a global patient-centred approach. A bundled payment system would seem more appropriate according to the scientific literature (Quinn et al, 2017). Bundled payment actually refers to, "a fixed payment that includes the prices of a group of services that would typically treat an episode of care in a defined period of time" (Quinn et al, 2017, p. 114).…”
Section: International Review Of Public Policy 2:3 | 2020mentioning
confidence: 99%
“…More recent data from the Massachusetts Behavioral Health Partnership (MBHP), a Beacon Health Options company which manages behavioral health for many Massachusetts Medicaid enrollees, found that 57.7% of those receiving detox services in FY2011 had two or more admissions that year, and that this group of “repeaters” accounted for 87% of all detox admissions that year [ 6 ]. Repeated admissions to detox without engagement in follow-up care represent lost opportunities for recovery, highlight inadequate access to a limited resource, and come at significant human and financial costs [ 5 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…SUD treatment typically pays fee-for-service (FFS), which has both strengths and weaknesses. FFS payments incentivize more care and provide higher payments for clients needing more care [ 7 , 12 , 13 ]. FFS payments do not reward quality care and restrict the scope of services covered (e.g.…”
Section: Introductionmentioning
confidence: 99%